GABAergic inhibition in visual cortical plasticity - Sale, Alessandro; Berardi, Nicoletta; Spolidoro, Maria; Baroncelli, Laura; Maffei, Lamberto (Frontiers in Cellular Neuroscience, 2010)
Experience is required for the shaping and refinement of developing neural circuits during well defined periods of early postnatal development called critical periods. Many studies in the visual cortex have shown that intracortical GABAergic circuitry plays a crucial role in defining the time course of the critical period for ocular dominance plasticity. With the end of the critical period, neural plasticity wanes and recovery from the effects of visual defects on visual acuity (amblyopia) or binocularity is much reduced or absent. Recent results pointed out that intracortical inhibition is a fundamental limiting factor for adult cortical plasticity and that its reduction by means of different pharmacological and environmental strategies makes it possible to greatly enhance plasticity in the adult visual cortex, promoting ocular dominance plasticity and recovery from amblyopia. Here we focus on the role of intracortical GABAergic circuitry in controlling both developmental and adult cortical plasticity. We shall also discuss the potential clinical application of these findings to neurological disorders in which synaptic plasticity is compromised because of excessive intracortical inhibition.